(untitled) (American Journal of Islam and Society, 1998)
This paper seeks to advance an understanding of Human Nature through Islamic Sources. The paper also seeks to adopt a self-consciously comparative approach to psychology, comparing Islamic perspective with Western views. The author explores Islamic views on the three dimensions of psychology - the spiritual, the physiological and the behavioral. The paper concludes by emphasizing the need for a theoretical basis to define the psychological vision of human nature and to identify the subject matter of psychology within Islamic framework. Psychology cannot be separated from religious, philosophical and moral issues, the paper insists, therefore it is important that they be integrated in the efforts to articulate Islamic psychology.